Utility of inline milk fat and protein ratio to diagnose subclinical ketosis and to assign propylene glycol treatment in lactating dairy cows - Jenkins, Nicholas T.; Pena, Gustavo; Risco, Carlos; Barbosa, Carolina C. [UNESP]; Vieira-Neto, Achilles; Galvao, Klibs N. (Canadian Vet Med Assoc, 2015)
The objective was to identify a fat-to-protein ratio (FPR) cut-off to diagnose subclinical ketosis (SCK) and to evaluate the effect of propylene glycol (PPG) treatment of cows with high FPR. The optimized cut-off was > 1.42; sensitivity (Se) = 92%; specificity (Sp) = 65%. A cut-off > 1.5 was selected for the PPG trial for balanced Se-Sp. Fat-to-protein ratio cut-offs > 1.25, 1.35, 1.50, 1.60, and 1.70 resulted in Se-Sp of 100% to 49%, 96% to 59%, 75% to 78%, 33% to 90%, and 8% to 96%, respectively. The proportions of cows with FPR > 1.25, 1.35, 1.42, 1.50, 1.60, and 1.70 were 60%, 50%, 44%, 30%, 14%, and 6%, respectively. Incidences of clinical ketosis and milk yield were similar between cows that received 400 mL of PPG (n = 34) and control cows (n = 38). Prevalence of SCK at enrollment was 29.2%; therefore, FPR > 1.5 is not indicated for treatment. Lower cut-offs should be used for screening.